Two Ways to God in Thomas Aquinas and Michel Henry - Nemes, Steven ca. 20./21. Jh. (Journal for continental philosophy of religion, 2021)
Abstract One can discern passages in the writings of the Scholastic doctor Thomas Aquinas and the contemporary French phenomenologist Michel Henry which can be interpreted as putting forth very similar ways for grasping the existence of God. These “ways to God” can be fruitfully compared from the point of view of their philosophical starting points as well as of their consequences for theological epistemology. The purpose of the present essay is to pursue this comparative work and to see what philosophical-theological fruit it can yield.